Anodic passivation on the recycling of cemented carbide scrap by selective electro-dissolution. (October 2018) - Sun, Fenglong; Chen, Xingyu; Zhao, Zhongwei
Highlights: Electrochemistry was used in selective electro-dissolution for WC-Co scrap. The mechanism of anodic passivation was displayed in this paper. The lower diffusion of cation in the porous WC layer was calculated. The electro-dissolution can't meet application for the low dissolving rate. Abstract: Selective dissolution is an effective method to recycle WC and Co from cemented carbide scrap, and the electro-dissolution process is considered competitive. However, the anodic passivation slows down oxidation and leads to inefficiency during electrolysis. The porosity of the WC coat is the main impact factor for passivation. Thus, in this study, types of WC-Co cemented carbide (YG8/YG15/YG20) with different bonding phase content were studied in the acid electrolyte through electrochemistry tests. The thickness of the coat was measured, and the diffusion coefficients ( Di ) were calculated by Fick's first law of diffusion. The Di of cation was 0.088 × 10 − 10, 0.61 × 10 − 10, 0.70 × 10 − 10 m 2 s − 1 for YG8, YG15, YG20, respectively. The inferior diffusion coefficient resulting from the dense coat was believed to be the main reason for the low dissolving rate.